Analisis Dampak Parameter Debu PM10 di Udara terhadap Masyarakat di Desa Sangi-Sangi - Sapitri, Asna Wulan; Sumarlin, Sumarlin; Assiddieq, Moch. (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2023)
Air pollution is the entry or inclusion of a substance, energy, life or other component into the environment so as to change the normal air composition due to human activities or natural processes so that it can result in poor air quality and does not function as it should, Particulate Matter 10 (PM10) is one type of air pollution that can come from various sources including human activities and natural sources. Based on the results of the above research that the existence of mining operations has a positive impact and also a negative impact. The positive impact is the increase in income or the economy of the community obtained from mining, while the negative impact is that it causes damage to the environment and the emergence of air pollution due to mining activities and if exposed continuously to dust in the air can cause problems with human breathing. The concentration of PM10 was measured using the Air Quality Monitor tool. This study shows the results of measuring the concentration of PM10 of Sangi-sangi village in the mining area at the location of sample point one the highest concentration value is 30.17 μg/Nm3 which occurs at noon at 13.00-14.00, while the results of measuring the concentration of PM10. at the location of sample two the highest value of concentration results occurs in the afternoon at 13.00-14.00 has a concentration value of 29.17 μg/Nm3.